2014
DOI: 10.5051/jpis.2014.44.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Serum level changes of long chain-polyunsaturated fatty acids in patients undergoing periodontal therapy combined with one year of omega-3 supplementation: a pilot randomized clinical trial

Abstract: PurposeWe aimed to investigate the impact of nonsurgical periodontal treatment combined with one-year dietary supplementation with omega (ω)-3 on the serum levels of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and arachidonic acid (AA).MethodsFifteen patients with chronic generalized periodontitis were treated with scaling and root planing. The test group consisted of seven patients (43.1±6.0 years) supplemented with ω-3, consisting of EPA plus DHA, three capsules, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 30 publications
(38 reference statements)
3
62
1
Order By: Relevance
“…In the presence of aspirin, acetylated cyclooxygenase‐2 converts DHA into 17‐hydroxy‐DHA, which leads to aspirin‐triggered resolvins with enhanced proresolution effects. Neither supplementation of n‐3s nor aspirin by itself significantly impacts periodontitis in humans 28–30 . Cumulatively, these studies suggest that n‐3s + aspirin have clear and potentially clinically important anti‐inflammatory actions 8,10,31‐33 …”
Section: Discussionmentioning
confidence: 97%
“…In the presence of aspirin, acetylated cyclooxygenase‐2 converts DHA into 17‐hydroxy‐DHA, which leads to aspirin‐triggered resolvins with enhanced proresolution effects. Neither supplementation of n‐3s nor aspirin by itself significantly impacts periodontitis in humans 28–30 . Cumulatively, these studies suggest that n‐3s + aspirin have clear and potentially clinically important anti‐inflammatory actions 8,10,31‐33 …”
Section: Discussionmentioning
confidence: 97%
“…In the studies where omega-3 PUFAs were used alone, no significant differences in clinical parameters between the study and control groups have been demonstrated, [26] or significant improvement of probing depth (PD), CAL, gingival index (GI), and bleeding on probing (BOP) has been shown. [9] Furthermore, in the patients receiving omega-3 PUFAs a ratio of AA to EPA decreased significantly, reaching the level of 7:1, whereas in the control group this ratio remained high (18:1). [10,26] Long-term administration of omega-3 PUFAs resulted also in increased plasma level of EPA.…”
Section: Omega-3 Pufa Use In the Treatment Of Periodontitismentioning
confidence: 95%
“…[26] Omega-3 PUFA administration resulted in the reduction of inflammatory mediators such as TNF-α or C-reactive protein (CRP). [9] For maintaining health, an optimal ratio of omega-6 fatty acids to omega-3 fatty acids was set at 4:1-5:1 and not exceeding 10:1. [9] Furthermore, in the patients receiving omega-3 PUFAs a ratio of AA to EPA decreased significantly, reaching the level of 7:1, whereas in the control group this ratio remained high (18:1).…”
Section: Omega-3 Pufa Use In the Treatment Of Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In order to provide a better treatment modality to patients who are highly susceptible to periodontal diseases, host modulation using various therapeutic agents targeting the manipulation of the inflammatory pathway has been proposed as an adjunctive treatment with conventional periodontal therapy. [10][11][12][13] Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most potent agents due to their direct inhibition of cyclooxygenase, which is responsible for the production of arachidonic acid metabolites. These metabolites are involved in tissue breakdown in periodontal diseases 14 via the activation of the secretion of matrix metalloproteinase and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%